1992
DOI: 10.1136/oem.49.2.113
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the time course from human dietary exposure to polycyclic aromatic hydrocarbons to urinary elimination of 1-hydroxypyrene.

Abstract: The significance of diet as an exposure route for polycyclic aromatic hydrocarbons (PAHs) and the associated kinetics of urinary 1-hydroxypyrene (1-OHPY) elimination were examined through a controlled human exposure study. Results showed that a 100 to 250-fold increase in a dietary benzo(a)pyrene (BaP) PAHs is potentially substantial and therefore it is likely to be a confounding cofactor in its effect on urinary 1-OHPY concentrations when trying to isolate the effect of other exposure routes. The present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
114
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 29 publications
2
114
0
1
Order By: Relevance
“…The half-life for urinary 1-PYR in humans has been reported to be 9.8 hours (Brzeznicki et al 1997) and 6-35 hours (Jongeneelen et al 1990) after inhalation exposure, 4.4 hours (Buckley and Lioy 1992) and 12 hours after ingestion exposure, 11.5-15 hours after dermal absorption , and 3.9-26.7 hours (average 10.4 hours) after inhalation and dermal absorption (Boogaard and van Sittert, 1994). Information on half-lives of the other OH-PAHs is scarce; however, since these are the same group of metabolites formed under similar biological pathways, we can reasonably deduce that other OH-PAHs measured in this study would have similar half-lives.…”
Section: Introductionmentioning
confidence: 99%
“…The half-life for urinary 1-PYR in humans has been reported to be 9.8 hours (Brzeznicki et al 1997) and 6-35 hours (Jongeneelen et al 1990) after inhalation exposure, 4.4 hours (Buckley and Lioy 1992) and 12 hours after ingestion exposure, 11.5-15 hours after dermal absorption , and 3.9-26.7 hours (average 10.4 hours) after inhalation and dermal absorption (Boogaard and van Sittert, 1994). Information on half-lives of the other OH-PAHs is scarce; however, since these are the same group of metabolites formed under similar biological pathways, we can reasonably deduce that other OH-PAHs measured in this study would have similar half-lives.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, predominantly focused on 1-PYR, have been conducted to estimate half-life (t 1/2 ) from various exposure routes. The t 1/2 after inhalation exposure has been determined to be 6.0-29 h. [12][13][14] For ingestion exposure, the 1-PYR t 1/2 was reported to be 4.4-12 h. [15][16][17] For dermal absorption, the 1-PYR t 1/2 was estimated at 11.5-15 h. 17,18 In several occupational studies on workers exposed through both inhalation and dermal absorption, the average t 1/2 ranged 10.4-18 h. [19][20][21] Increasingly, PAH biomonitoring studies are being carried out using multiple biomarkers in addition to 1-PYR. Some biomarkers or metabolic patterns have been proposed to be associated with specific sources or risk factors due to the change of enzyme polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that pyrene was rapidly distributed, metabolized, and eliminated from the body, and 1-OHP in urine represented a constant fraction (2%) of total pyrene intake in urine and feces (Bouchard et al, 1998). The half-life of urinary 1-OHP excretion ranges from 4 to 35 h (Jongeneelen et al, 1990;Boogaard and van Sittert, 1994) and the excretion declines to near baseline concentrations within 48 h following an exposure event (Buckley and Lioy, 1992). Thus, urinary 1-OHP may be used to assess individuals' recent PAH exposure.…”
Section: Introductionmentioning
confidence: 99%